PENGEMBANGAN SISTEM INFORMASI PENGUSULAN JABATAN FUNGSIONAL AKADEMIK DOSEN BERBASIS WEB PADA STEKOM SEMARANG - Ester Yuli Suprapti; Priyo Wibowo (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2021)
High School of Electronics and Computers (STEKOM) Semarang, based on Jl. Majapahit 605, has several campuses in Semarang and outside Semarang. With the condition of the campus location, it makes it difficult for lecturers and related parties to process the proposal for the Academic Functional Position (JAFA). Lecturers have to repeatedly go to the central campus to process JAFA proposals and lecturers cannot directly know the extent of the credit score that has been generated. Other related parties such as the staffing department, the Credit Score Assessment Team (TPAK) and the STEKOM Leaders have difficulty monitoring the activities of lecturers in carrying out their tridharma duties. Web-based Lecturer Academic Functional Position Proposal Information System which was developed using the Research and Development (R&D) method produces an application that will solve the problems surrounding the JAFA proposal at STEKOM and can answer STEKOM's need for an Information system for lecturer JAFA proposals without being limited by place and time. . In making this system, the author uses Macromedia Dreamweaver MX 2004 software as the design media and PHP as the programming language used, and the MySql database as storage media